The tRNA-Derived Fragment-3017A Promotes Metastasis by Inhibiting NELL2 in Human Gastric Cancer - Tong, Linhao; Zhang, Weixu; Qu, Bicheng; Zhang, Fei; Wu, Zhonghua; Shi, Jinxin; Chen, Xiaowan; Song, Yongxi; Wang, Zhenning (Frontiers in Oncology, 2021)
tRNA-derived fragments (tRFs) are a new classification of small non-coding RNAs (sncRNAs) derived from the specific cleavage of precursors and mature tRNAs. Accumulating recent evidence has shown that tRFs are frequently abnormal in several cancers. Nevertheless, the role of tRFs in gastric cancer and its mechanism remain unclear. In this study, we found abnormal expression of tRF-3017A (derived from tRNA-Val-TAC) in gastric cancer tissues and cell lines and confirmed its effect on promoting the invasion and migration of gastric cancer cells through functional experiments in vitro. Analysis of clinicopathologic data showed patients with higher tRF-3017A were associated with significantly higher lymph node metastasis. Mechanistic investigation implies that tRF-3017A regulates the tumor suppressor gene NELL2 through forming the RNA-induced silencing complex (RISC) with Argonaute (AGO) proteins. In this study, we found that higher tRF-3017A were associated with significantly higher lymph node metastasis in gastric cancer patients and the tRF-3017A may play a role in promoting the migration and invasion of gastric cancer cells by silencing tumor suppressor NELL2.